Explicar la importancia del proceso de la revolucin neoltica - Baca Amasifuen, Angela Katherine (2019)
At a certain point in the historical-cultural sequence, which never predates the 8th millennium BC, there is a phenomenon of enormous significance in all orders of culture economic, social, ideological, in remote and independent areas of geography of the planet. This phenomenon is manifested in the appearance of a series of archaeologically detectable material elements: ceramic, polished stone, permanent or semi-permanent room in villages, domesticated animals or plants, etc. Both denominations can serve as a starting point for the development of the issue, since, in fact, the Neolithic can be seen from two points of view: as an archaeological phase defined by a set of material features or as a stage the general evolution of humanity. Until very recent ones the Neolithic has always been addressed from the first perspective, due to the very conditions of the emergence of Prehistory as a science and the kind of evidence available to judge the nature of the changes that he intended to explain.